ISOLASI DAN IDENTIFIKASI SENYAWA KIMIA DARI SPONS DI PERAIRAN LAUT SULAWESI - Jenny Kumajas (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
It has been conducted a research of the isolation and identification of chemical compound from the spons in Sulawesi sea waters. The purpose of this study was to isolate and identify chemical compound from spons Cliona celata in Sulawesi sea waters. Isolation was carried out by extraction with ethanol 70% and partitioning with ethyl acetate. The separation was carried out using thin layer chromatography (TLC) and column chromatography. Identification of structure of the compound was done by mass spectrophotometry gas chromatography technique. The isolation results obtained the ethyl acetate fraction eluate vial-123 (0.2 mg) was determined as a compound with the proposed 2-methyl-1,3,5-trioxane.